Focal Spot Size Estimation for a 4 MeV Small-size Betatron Using Digital X-ray Detector; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Sukharnikov K. V. Konstantin Vladimirovich (2016, 2016)
Title screen